Application of Empirical Best Linear Unbiased Prediction (EBLUP) in Estimating Labor Force Participation Rate at the Regency/City Level in Kalimantan Island, 2016 - Izumi Citra Amelia; Riski Tommi Mardoni; Syofmarlianisyah Putri; Debby Cynthia Ningrum; Iftina Ika Rahmawati; Cucu Sumarni (Jurnal Statistika Universitas Muhammadiyah Semarang, 2025)
The Labor Force Participation Rate (LFPR) serves as a vital indicator for labor market planning, particularly in Kalimantan, a region experiencing sustained economic growth. In 2016, however, regency- and city-level LFPR data were unavailable due to a reduced sample size in the National Labor Force Survey. This study employs Small Area Estimation (SAE) using the Empirical Best Linear Unbiased Prediction (EBLUP) method to estimate LFPR at the sub-provincial level. Auxiliary variables include the number of vocational high schools (SMK), the proportion of villages receiving foreign aid, the share of trade-related enterprises, and the number of villages with migrant workers. Findings indicate that SAE-EBLUP produces estimates with lower relative standard errors (RSE) than direct estimation, offering improved precision for small-area LFPR estimates.